Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Karang Hias di PT. Panorama Alam Tropika Jakarta Selatan - Mirnawati Mirnawati; Budiman Haruna; Karma Karma (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of service quality on Karang Hias customer satisfaction at PT. Panorama Alam Tropika, South Jakarta. The sample used was 30 ornamental coral customers who purchased ornamental corals. The sampling technique in this research used a non-probability sampling method and a side purposive technique. Data collection was carried out using a questionnaire with a Likert scale. The analytical method used in this research is a simple regression analysis method with the SPSS 23 application. The research results based on (t test) show that service quality has a significant effect on customer satisfaction with a significance value of 0.001 < 0.05. The results of the Coefficient of Determination test obtained an R Square of 0.931. This shows that the dependent variable of customer satisfaction is 93% influenced by the independent variable service quality, while 7% is influenced by other variables that have not been examined in this research.